First experience of SARS‐CoV‐2 infections in solid organ transplant recipients in the Swiss Transplant Cohort Study. Issue 10 (9th June 2020) - Tschopp, Jonathan; L'Huillier, Arnaud G.; Mombelli, Matteo; Mueller, Nicolas J.; Khanna, Nina; Garzoni, Christian; Meloni, Dario; Papadimitriou‐Olivgeris, Matthaios; Neofytos, Dionysios; Hirsch, Hans H.; Schuurmans, Macé M.; Müller, Thomas; et al.
Abstract : Immunocompromised patients may be at increased risk for complications of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection. However, comprehensive data of SARS‐CoV‐2 infection in solid organ transplant (SOT) recipients are still lacking. We performed a multicenter nationwide observational study within the Swiss Transplant Cohort Study (STCS) to describe the epidemiology, clinical presentation, treatment and outcomes of the first microbiologically documented SARS‐CoV‐2 infection among SOT recipients. Overall, 21 patients were included with a median age of 56 years (10 kidney, 5 liver, 1 pancreas, 1 lung, 1 heart and 3 combined transplantations). The most common presenting symptoms were fever (76%), dry cough (57%), nausea (33%), and diarrhea (33%). Ninety‐five percent and 24% of patients required hospital and ICU admission, respectively, and 19% were intubated. After a median of 33 days of follow‐up, 16 patients were discharged, 3 were still hospitalized and 2 patients died. These data suggest that clinical manifestations of SARS‐CoV‐2 infection in middle‐aged SOT recipients appear to be similar to the general population without an apparent higher rate of complications. These results need to be confirmed in larger cohorts. Abstract : This study describes the epidemiology, clinical presentation, treatment, and outcome of the first 21 solid organ transplant recipients infected with SARS‐CoV‐2 in the Swiss Transplant Cohort Study.